Study on Composite Design Suitable for High Hardness and Strong Abrasive Formation - Song, Dongdong; Yang, Yingxin; Ren, Haitao (Journal of Advanced Thermal Science Research, 2021)
PDC (Polycrystalline Diamond Compact bit) composite is the most important cutting element of petroleum bit, which performance directly affects the service effect and service life of the bit. During the drilling process, the cutter will produce a large amount of friction heat when cutting the rock, resulting in a sharp increase in the internal temperature of the cutter. When the temperature reaches a certain value, thermal wear and tear are very easy to occur, which will not only cause diamond delamination but also reduce the wear resistance of the cutter. Under the action of impact load, impact failure is more likely to occur, which greatly reduces the service life of the cutter and the rock-breaking efficiency of the drill bit. Therefore, this paper studies the composite interface suitable for high-temperature drilling through the changes of cutting tooth temperature field and stress field with different interface shapes, which shows that the non-planar interface is more suitable for improving the cutting tooth life of composite under the action of comprehensive stress field.